Irish Emigration and Canadian Settlement: Patterns, Links, and Letters - Akenson, Donald Harman (Labour / Le Travail, 1991)
The article reviews the book, "Irish Emigration and Canadian Settlement: Patterns, Links and Letters," by Cecil J. Houston and William J. Smyth.
Keywords: BOOKS -- Reviews; EMIGRATION & immigration; HOUSTON, Cecil J.; IRISH Emigration & Canadian Settlement: Patterns, Links & Letters (Book); Nonfiction; SMYTH, William J.